2016
DOI: 10.3389/fendo.2016.00074
|View full text |Cite
|
Sign up to set email alerts
|

MR-Based Assessment of Bone Marrow Fat in Osteoporosis, Diabetes, and Obesity

Abstract: Bone consists of the mineralized component (i.e., cortex and trabeculae) and the non-mineralized component (i.e., bone marrow). Most of the routine clinical bone imaging uses X-ray-based techniques and focuses on the mineralized component. However, bone marrow adiposity has been also shown to have a strong linkage with bone health. Specifically, multiple previous studies have demonstrated a negative association between bone marrow fat fraction (BMFF) and bone mineral density. Magnetic resonance imaging (MRI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 73 publications
3
64
0
Order By: Relevance
“…Multiple studies demonstrated the ability of bone microstructure parameters as surrogate marker of bone quality to improve fracture risk prediction beyond BMD . The bone marrow as a nonmineralized bone component has recently drawn attention with regard to the pathogenesis of osteoporosis . The bone marrow affects bone metabolism in several ways.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…Multiple studies demonstrated the ability of bone microstructure parameters as surrogate marker of bone quality to improve fracture risk prediction beyond BMD . The bone marrow as a nonmineralized bone component has recently drawn attention with regard to the pathogenesis of osteoporosis . The bone marrow affects bone metabolism in several ways.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…Protonmagnetic resonance spectroscopy ( 1 H-MRS) is considered the MRI gold standard for bone marrow fat quantification, and point-resolved spectroscopy (PRESS) and stimulated echo acquisition mode (STEAM) single-voxel 1 H-MRS pulse sequences have been commonly used for the characterization of the fat spectrum in the bone marrow at the pelvis, spine, and hip (95). Images are acquired using dedicated coils to detect and quantify frequency signals of water, lipids, and other metabolites, expressed as universal ppm (parts per million) units with evaluation of areas under the peaks.…”
Section: Mrimentioning
confidence: 99%
“…Some evidence suggests that bone marrow adipocytes inhibit osteoblast activity and may promote osteoclast differentiation (57). Clinically, increased marrow fat measured by magnetic resonance imaging (MRI) or 1 H-MR spectroscopy ( 1 H-MRS) has been reported in subjects with decreased bone mineral density (BMD) (811), as well as in other pathologies including anorexia nervosa and diabetes, which were nicely reviewed in references (1214). …”
Section: Introductionmentioning
confidence: 99%